Defining and Measuring Cyberbullying Within the Larger Context of Bullying Victimization - L. Ybarra, Michele; boyd, danah; D. Korchmaros, Josephine; Oppenheim, Jay (Koby) (Journal of Adolescent Health, 2012)
Purpose: To inform the scientific debate about bullying, including cyberbullying, measurement. Methods: Two split-form surveys were conducted online among 6–17-year-olds (n = 1,200 each) to inform recommendations for cyberbullying measurement. Results: Measures that use the word “bully” result in prevalence rates similar to each other, irrespective of whether a definition is included, whereas measures not using the word “bully” are similar to each other, irrespective of whether a definition is included. A behavioral list of bullying experiences without either a definition or the word “bully” results in higher prevalence rates and likely measures experiences that are beyond the definition of “bullying.” Follow-up questions querying differential power, repetition, and bullying over time were used to examine misclassification. The measure using a definition but not the word “bully” appeared to have the highest rate of false positives and, therefore, the highest rate of misclassification. Across two studies, an average of 25% reported being bullied at least monthly in person compared with an average of 10% bullied online, 7% via telephone (cell or landline), and 8% via text messaging. Conclusions: Measures of bullying among English-speaking individuals in the United States should include the word “bully” when possible. The definition may be a useful tool for researchers, but results suggest that it does not necessarily yield a more rigorous measure of bullying victimization. Directly measuring aspects of bullying (i.e., differential power, repetition, over time) reduces misclassification. To prevent double counting across domains, we suggest the following distinctions: mode (e.g., online, in-person), type (e.g., verbal, relational), and environment (e.g., school, home). We conceptualize cyberbullying as bullying communicated through the online mode.